Evaluasi Karakteristik Sensori Ekoenzim dengan Penambahan Khamir dan Kombinasi Kulit Buah - Nuraisyah Binte Zainal; Oktira Roka Aji; Ambar Pratiwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
One of the main issues still faced by Indonesia is organic waste. This problem can be overcome by processing organic waste into eco-enzymes. Eco-enzymes contain alcohol and acetic acid, so they can be used as disinfectants and floor cleaners, dishwashing liquids, and detergents. This study aims to determine sensory characteristics such as aroma and color preferred by subjects for eco-enzyme production with the addition of yeast (Saccharomyces cerevisiae) and fruit peel variations. All eco-enzymes were made from organic waste in the form of fruit peel mixed with sugar and water in a ratio of 3:1:10. To determine the effect of yeast addition, eco-enzymes were made with orange peel with 2 variations, namely: 1) with the addition of yeast; and 2) without the addition of yeast. In the analysis of the effect of fruit peel variations, eco-enzymes were made with 6 variations, namely: 1) orange peel; 2) orange peel and pineapple peel; 3) orange peel and banana peel; 4) orange peel and papaya peel; 5) orange peel and apple peel; and 6) a mixture of all fruit peels. After one month of fermentation, the obtained eco-enzyme products were analyzed for their sensory properties. According to the observations, the aroma characteristic of the obtained eco-enzymes is that all eco-enzyme products, on average, have a normal fermentation sour aroma, with the exception of eco-enzyme products with added yeast, which have a sharper alcohol aroma. Observations on the sensory properties of color showed that eco-enzymes have a characteristic color ranging from dark brown to light brown. Overall, most of the panelists preferred the aroma and color of eco-enzymes produced without the addition of yeast. Meanwhile, for different fruit peel variations, the panelists preferred the mixture of fruit peels compared to other variations.